NOVEL METHOD THYROID HORMONE MEASUREMENT - Ari Tri Wanodyo Handayani (UNEJ e-Proceeding)
Iodine is an essential mineral of thyroidhormones produced by the thyroid gland. These areessential for life which therefore, makes iodinecrucial. Although goiter is the most visible sequelaeof iodine deficiency, the major impact ofhypothyroidism due to iodine deficiency (1). Thereare 2 billion people are at risk of goiter due toinsufficient intake of iodine. Nearly 266 millionschool-aged children world-wide have insufficientiodine intake (2). The school children formedrepresentative study population for iodine statusestimation as they represent community (3).Decreased thyroid hormones levels(hypothyroidism), by contrast, is associated withdecreased metabolic rate. Most of these effects aredue to the direct action of thyroid hormones ontarget tissues and direct actions on genes expression(4).Thyroid stimulating hormone (TSH),secreted by the anterior pituitary in response tofeedback from circulating thyroid hormone. TSHregulates iodide uptake mediated by thesodium/iodide symporter, followed by a series ofsteps necessary for normal thyroid hormonesynthesis and secretion. Thyroid hormone isessential for normal development, growth, neuraldifferentiation, and metabolic regulation (5).Although the presence of thyroid hormoneis crucial, it has not become part of a routine checkup on the public service because it is costly. Centralpublic health laboratory does not serve the thyroidhormone tests (6). Besides, blood test to measurethyroid hormone is considered quite painful. Lately,research on oral fluid (saliva) which can be used asthe unit of test analysis emerged. saliva can be seenin many cases as a reflection of the physiologicalfunction of the body. There have been concernsabout the use of saliva for diagnostic purposes dueto its low concentration of analytes in comparison toblood (7). However, the examination of the thyroidhormones using saliva have not been used. Thepresent investigation was aimed to analyze thethyroid hormone assays using saliva.MATERIAL AND METHODSThe research was an experimental laboratory. Theused animals were male Wistar rats aged 10-11weeks as many as 21 rats which were divided into 3groups. K was control group which received the 6-week standard food and drink. P1 was the firsttreatment group (iodine deficiency) which receivedPTU (6mg/kg/BW) using intragastric intubationmethod for 6 weeks. P2 was the second treatmentgroup which received PTU (6mg/kg/BW) usingintragastric intubation method for 6 weeks followedby Levothyroxine (10μg/100mg/BW) administrationusing the same method for 4 weeks. At the end ofthe study, saliva and blood of rats was taken andthen the rats were sacrificed. The specimen wereexamined for the levels of T3, T4, TSH using ELISAprocedure using Rat U-T3 (UltrasensitivityTriiodothyronine) kit, Catalog No: E-EL-R1050(Elabscience); Rat T4 (Thyroxine) kit, Catalog No: EEL-R0981 (Elabscience); and Rat TSH (ThyroidStimulating Hormone) kit, Catalog No: E-EL-R0976(Elabscience). The data were collected andstatistically analyzed using ANOVA Mutivariate.